The Creation of Chinese Educational Resources for Sixth Grade Students - Supinya Ruankaew; Ninlawan Saisombat; Suttida Mungkarat; Oatthaphon Boontanai (Journal of Educational Issues, 2024)
The majority of the Chinese teaching resources for sixth graders are textbooks that originate in China. These textbooks are written at a level that is too advanced for sixth graders. The purpose of this project is to generate teaching materials in Chinese for students in the sixth grade. The research is conducted using a pretest and posttest method, the sample consists of students in the sixth grade, and the research instruments consist of Chinese teaching materials, Chinese exercises, academic achievement exams, and a learning satisfaction questionnaire. The findings revealed that the average score on the pre-school achievement exam for the 44 kids who participated in the research was 45.34 percent, but the post test score was 82.39 percent. The standard deviation of the scores on the pre-test was 3.08 percent, whereas on the post-test it was 1.62 percent. This paper indicated that students had significant differences in their pre-test and post-school accomplishment at the level of 0.05, and postschool achievement scores were greater than pre-test achievement scores. In addition, students were highly happy with the Chinese language teaching materials.